Ijtihad Rasulullah S.A.W: Perbahasan Ulama dan Pengertian Mengenai Kesalahan dalam Berijtihad oleh Baginda S.A.W. - Abdul Majid, Latifah (Jurnal Usuluddin, 2001)
Basically, every ulama believes in the importance of ijtihad however they differ in their opinion as to whether ijtihad exists in the sense of reality. Some ulama believe that ijtihad exists based on reality because direction From Allah the Almighty came to Prophet Muhammad (p.b.u.h) in the form of revelation as basis for ijtihad made by the Prophet (p.b.u.h). These differences in opinion are based on verses in the Qur’an (ayat ’itab) and on the hadith.